Bile reflux alters the profile of the gastric mucosa microbiota - Huang, Gang; Wang, Sui; Wang, Juexin; Tian, Lin; Yu, Yanbo; Zuo, Xiuli; Li, Yanqing (Frontiers in Cellular and Infection Microbiology, 2022)
Background Bile reflux can cause inflammation, gastric mucosa atrophy, and diseases such as stomach cancer. Alkaline bile flowing back into the stomach affects the intragastric environment and can alter the gastric bacterial community. We sought to identify the characteristics of the stomach mucosal microbiota in patients with bile reflux. Methods Gastric mucosal samples were collected from 52 and 40 chronic gastritis patients with and without bile reflux, respectively. The bacterial profile was determined using 16S rRNA gene analysis. Results In the absence of H. pylori infection, the richness (based on the Sobs and Chao1 indices; P <0.05) and diversity (based on Shannon indices; P <0.05) of gastric mucosa microbiota were higher in patients with bile reflux patients than in those without. There was a marked difference in the microbiota structure between patients with and without bile reflux (ANOSIM, R=0.058, P=0.011). While the genera, Comamonas, Halomonas, Bradymonas, Pseudomonas, Marinobacter, Arthrobacter, and Shewanella were enriched in patients with bile reflux, the genera, Haemophilus, Porphyromonas, and Subdoligranulum, were enriched in those without bile reflux. Conclusion Our results demonstrate that bile reflux significantly alters the composition of the gastric microbiota.